Simulation of Productive Processes in Living Labs: A Support Tool for Decision-Making from an Ergonomic Perspective - Galvez-Manriquez, D; Santander-Tapia, P; Delgado-Cadena, L (Springer Nature, 2024)
The ergonomics of workers in production processes has a direct impact on the efficiency and effectiveness of the process. For this reason, various authors have been interested in evaluating multiple physiological factors with the aim of determining actions that generate greater stress in employees in order to prevent accidents and improve production processes. However, evaluating ergonomics in the workplace is not a simple task. This article proposes the use of Living Lab-type laboratories to carry out simulations of production processes and to measure the level of stress and ergonomics of workers while performing their tasks. The goal is to generate a simulation and evaluation protocol that allows for both quantitative and qualitative assessment of worker ergonomics when carrying out an activity, ultimately providing information for process improvement. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2024.